2023
DOI: 10.3390/su15032362
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Preferences and Perceptions Regarding Online versus Offline Teaching and Learning Post-COVID-19 Lockdown

Abstract: The COVID-19 pandemic at its peak compelled students to stay home and adapt to the distance learning system. The world has gone through phases of fear and respite in the recent years. There have been a number of studies related to student learning via online teaching during the pandemic. Now, as the vaccination coverage picks up and the pandemic appears to have achieved a plateau, it is time to take a view of students’ perceptions of online learning and its effectiveness in skill development during the COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
1
8
0
2
Order By: Relevance
“…And 44% of the respondents eliminated their shyness to participate in questions and discussions. Figure 5 shows that 64% of the respondents do not achieve a better understanding with distance learning, which is in line with [43]'s results that an online synchronous delivery approach of environmental engineering does not maintain the same level of students' performance as in the hybrid delivery, but is in contrast with [23]'s findings, where the majority of students were more satisfied and comfortable in gaining knowledge and learning with online classes, as they also gain higher scores in exams. However, 72% of the respondents understand that remote learning is the future trend of education and learning; 78% love dealing with technology and acquiring new digital skills, and 71% feel that they gained the skill to rely on themselves.…”
Section: Domain 3: Students' Perceptions Towards the Remote Studying ...supporting
confidence: 73%
See 2 more Smart Citations
“…And 44% of the respondents eliminated their shyness to participate in questions and discussions. Figure 5 shows that 64% of the respondents do not achieve a better understanding with distance learning, which is in line with [43]'s results that an online synchronous delivery approach of environmental engineering does not maintain the same level of students' performance as in the hybrid delivery, but is in contrast with [23]'s findings, where the majority of students were more satisfied and comfortable in gaining knowledge and learning with online classes, as they also gain higher scores in exams. However, 72% of the respondents understand that remote learning is the future trend of education and learning; 78% love dealing with technology and acquiring new digital skills, and 71% feel that they gained the skill to rely on themselves.…”
Section: Domain 3: Students' Perceptions Towards the Remote Studying ...supporting
confidence: 73%
“…However, the conclusions of [23], who investigated students' preferences and perceptions towards offline and online learning post-COVID-19 lockdown at a Saudi University, contradict with the above findings. The findings of [23] revealed that a significant majority of students had a fear of catching the coronavirus and wished to pursue online classes as they faced time management issues, depression, and tiredness in the face-to-face mode of learning. The results of [24]'s study, which analyzed the move to emergency remote teaching at the School of Telecommunication Engineering in Madrid, show an increase in students' academic performance in emergency remote teaching.…”
Section: Background 1perceptions Towards the Remote Mode Of Learningmentioning
confidence: 76%
See 1 more Smart Citation
“…The easier accessibility of learning materials was evaluated as a positive aspect, while Slovak students also prefer remote exams. The time and cost savings from the absence of travel, flexible schedules, and home comfort, which are mentioned in the literature as essential positives [4,24,25,28,[31][32][33][34], were not mentioned as decisive factors for the students surveyed in this study. Even though the digital generation's use of IT devices and the Internet has recently increased, regardless of the pandemic, university students still use the materials and literature provided or recommended by the lecturer and do not take the trouble to search and develop literature on the subject themselves.…”
Section: Discussionmentioning
confidence: 96%
“…The survey revealed that the practice-oriented strategy was less effective in terms of results and, overall, the students were less satisfied with online education. In a study by Riaz et al [28] in Saudi Arabia, students were very positive about their home learning. People returning to universities after the closures complained about fatigue (77% of survey participants), demotivation, and unhappiness (63%).…”
Section: Literature Reviewmentioning
confidence: 94%